1979
DOI: 10.1093/geronj/34.5.704
|View full text |Cite
|
Sign up to set email alerts
|

Age Differences in the Effects of Perceptual Noise

Abstract: Elderly (60 to 82 years) and young (18 to 25 years) subjects were tested on a visual task in which noise items were present but did not require processing to test the hypotheses that elderly persons have more difficulty ignoring irrelevent stimuli and suppressing response competition than do younger persons. Tachistoscopically presented displays contained a precued central target letter either alone or flanked by noise items that required (1) a response the same as, or (2) opposite to that required by the targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
61
2

Year Published

1982
1982
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(67 citation statements)
references
References 32 publications
4
61
2
Order By: Relevance
“…There is some support that older adults are more vulnerable to stimulus than to response interference. One study reported equivalent effects of response competition between younger and older adults, whereas older adults were more vulnerable to perceptual interference from task-relevant distractors (Wright & Elias, 1979). At small set sizes, older adults were particularly vulnerable to perceptual interference, but older and younger adults showed equivalent interference effects at larger set sizes (Maylor & Lavie, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…There is some support that older adults are more vulnerable to stimulus than to response interference. One study reported equivalent effects of response competition between younger and older adults, whereas older adults were more vulnerable to perceptual interference from task-relevant distractors (Wright & Elias, 1979). At small set sizes, older adults were particularly vulnerable to perceptual interference, but older and younger adults showed equivalent interference effects at larger set sizes (Maylor & Lavie, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Age-related change in executive function (e.g., Baddeley, 1996), which is responsible for allocating attentional resources, also is a likely contributor to problems understanding one person while inhibiting messages from other talkers (Tun, et al, 2002). In fact, there is ample evidence that aging brings about a reduced ability to ignore irrelevant information (e.g., Hasher & Zachs, 1988;Kausler, 1982;Wright & Elias, 1979) and/ or difficulty discriminating relevant from irrelevant information (e.g., Plude & Hoyer, 1985).…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…Age-related change in executive function (e.g., Baddeley, 1996), which is responsible for allocating attentional resources, also is a likely contributor to problems understanding one person while inhibiting messages from other talkers (Tun, et al, 2002). In fact, there is ample evidence that aging brings about a reduced ability to ignore irrelevant information (e.g., Hasher & Zachs, 1988;Kausler, 1982;Wright & Elias, 1979) and/ or difficulty discriminating relevant from irrelevant information (e.g., Plude & Hoyer, 1985).The focus of the research presented in this paper is to better understand the degree to which (and why) older adults experience problems understanding speech in situations with more than one talker. This work is motivated by the large body of anecdotal and empirical evidence demonstrating that older adults, particularly those with hearing loss, have problems understanding speech that is masked by either noise or by other speech.…”
mentioning
confidence: 99%
“…The goal of the flankers was to produce perceptual interference. Using the Eriksen and Eriksen (34) filtering task, Wright and Elias (35) found that younger adults were more susceptible to the distractors than were the older adults.…”
Section: Evidence For Age Constancies In Selective Attentionmentioning
confidence: 99%